O próximo de Kierkegaard, o outro de Lévinas e a condição animal - Ferreira, Sandro de Souza (Universidade do Vale do Rio do Sinos, 2006)
Historically the condition of the animal has been treated by the light of moral perfectionism developed by Aristotle and Aquinas with small variations. Animals have a place in the world in order to serve man. The reaction to the perfectionist conception has become prominence in the Peter Singer’s and Tom Regan’s voices. They are philosophers dedicated to the exam of the animal condition. However, Singer’s propositions like Regan’s have been criticized by arguments that sometimes put them in trouble. An approach about animal condition which can at the same time to react to the moral perfectionism and to escape from the objections against Singer and Regan is not an easy task. Nevertheless, ethics can be thought from alterity on – in which responsibility assumes the main role – and it can be showed as a good way. In this context, stand out the names of Kierkegaard and Lévinas, philosophers that thought alterity and responsibility in an innovating ways. So, what is intended to analyze in this study are the perspe
Keywords: alteridade; condição animal; filosofia moral; Kierkegaard, Sören; Lévinas, Emmanuel; animals; neighbour; other; Kierkegaard, Lévinas; Ciências Humanas